Labeling the Stroma of a Patient‐Derived Orthotopic Xenograft (PDOX) Mouse Model of Undifferentiated Pleomorphic Soft‐Tissue Sarcoma With Red Fluorescent Protein for Rapid Non‐Invasive Imaging for Drug Screening. Issue 2 (12th July 2016) - Kiyuna, Tasuku; Murakami, Takashi; Tome, Yasunori; Igarashi, Kentaro; Kawaguchi, Kei; Russell, Tara; Eckardt, Mark A.; Crompton, Joseph; Singh, Arun; Bernthal, Nicholas; Bukata, Susan; Federman, Noah; et al.
ABSTRACT: Our laboratory pioneered patient‐derived orthotopic xenograft (PDOX) mouse models using surgical orthotopic implantation (SOI). PDOX models are patient‐like, in contrast to the ectopic subcutaneous‐transplant cancer models. In the present study, we demonstrate that an undifferentiated pleomorphic soft‐tissue sarcoma (UPS‐STS) PDOX model acquired bright RFP‐expressing stroma through one passage in red fluorescent protein (RFP) transgenic mice, which upon passage to non‐colored nude mice was non‐invasively imageable. A PDOX nude mouse model of UPS‐STS was established in the biceps femoris of nude mice. After the tumors grew to a diameter of 10 mm, the tumors were subsequently passaged to RFP transgenic mice, and after tumor growth were then passaged to non‐transgenic nude mice. Tumors were divided into small fragments and transplanted in the biceps femoris at each passage. The OV100 Small Animal Fluorescence Imaging System and FV1000 laser scanning confocal microscope were used to image RFP fluorescence in the UPS‐STS PDOX models. UPS‐STS PDOX tumors, previously grown in RFP transgenic nude mice for only one passage, had very bright fluorescence and after passage to non‐transgenic nude mice maintained the bright fluorescence and were non‐invasively imageable. FV1000 confocal imaging revealed diffusely distributed bright RFP stromal cells in the PDOX tumor, both in RFP transgenic mice and after passage to non‐transgenic mice. These results demonstrate a powerful method to make the PDOX UPS‐STS model brightly fluorescent for non‐invasive imaging, as well as for confocal microscopy of individual stromal cells associated with the tumor. The RFP‐labeled UPS PDOX has the potential to rapidly screen for novel effective agents for individual patients, including stroma‐targeting drugs, whereby the stromal cells are a visual target. J. Cell. Biochem. 118: 361–365, 2017. © 2016 Wiley Periodicals, Inc. Abstract : An imageable model of a soft‐tissue sarcoma patient‐derived orthotopic xenograft (PDOX) labeled in the stroma after one passage in a red fluorescent protein (RFP)‐expressing transgenic nude mouse and then passaged to a non‐transgenic nude mouse.